Controlled aqueous synthesis of ultra-long copper nanowires for stretchable transparent conducting electrode. Issue 7 (20th January 2016) - Hwang, Chahwan; An, Jihyun; Choi, Byung Doo; Kim, Kwanpyo; Jung, Soon-Won; Baeg, Kang-Jun; Kim, Myung-Gil; Ok, Kang Min; Hong, Jongin
Abstract : A stretchable transparent electrode was achieved with rationally-controlled ultra-long copper nanowires and low-temperature direct spray coating. Abstract : The environmentally benign synthesis of ultra-long copper nanowires with successful control of diameter and length for stretchable transparent conducting electrodes (TCEs) is reported. Ultra-long copper nanowires (CuNWs) with an average length of 92.5 μm (maximum length up to 260 μm) and an average diameter of 47 nm were synthesized using environmentally friendly water–alcohol mixtures andl -ascorbic acid as a reducing agent. A facile removal of insulating surface layers, such as organic capping molecules and copper oxide/hydroxide, by short-chain organic acid treatment allowed low contact resistance between the CuNWs without post-reductive treatment at elevated temperatures. The CuNWs were directly spray-coated on glass or polydimethylsiloxane (PDMS) at a low processing temperature of 130 °C. The CuNW TCE on a glass substrate exhibited a low sheet resistance of 23.1 Ohm sq −1 and a high optical transmittance of 84.1% at 550 nm. Furthermore, the CuNWs were directly spray-coated on stretchable PDMS, which showed a low sheet resistance of 4.1 Ohm sq −1 and a high optical transmittance of 70% at 550 nm.